2020
DOI: 10.1186/s13017-020-00324-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of risk factors in thoracic trauma patients with a comparison of a modern trauma centre: a mono-centre study

Abstract: Objectives Thoracic trauma (TT) is the third most common cause of death after abdominal injury and head trauma in polytrauma patients. Its management is still a very challenging task. The purpose of this study was to analyse the risk factors affecting the outcome in a high-volume trauma centre and the efficacy of a specialised trauma team in level 1 trauma centres. Patients and methods Between January 2003 and December 2012, data of all patients admitted to the accident… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
3
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 25 publications
1
43
3
4
Order By: Relevance
“…The present study found a lower incidence of thoracic trauma compared to that reported elsewhere [9,22,23]. This was probably underestimated herein as those suffering minor thoracic injuries (AIS Thorax =1), including single rib fractures, were excluded.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…The present study found a lower incidence of thoracic trauma compared to that reported elsewhere [9,22,23]. This was probably underestimated herein as those suffering minor thoracic injuries (AIS Thorax =1), including single rib fractures, were excluded.…”
Section: Discussioncontrasting
confidence: 61%
“…Although it is a register study with the known weaknesses, the present multicentre study is based on data prospectively collected over a 20-year-period from level I to III trauma centres and included patients of all ages whereas many studies focused on thoracic trauma are single centre studies and only included patients ≥ 16 years [5,8,12,17,22,37]. Thus, our ndings are generalisable to other high-income countries.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other nations, credits would be given to economic growth, and authorities efforts for continuously promoting public safety awareness, enforcing the use of helmets and seat-belts, combatting speeding and drunk driving, and advocating for safer vehicles over the years [ 12 , 14 , 15 ]. Furthermore, newly instituted regional trauma centers with standardized, optimized managing protocol and dedicated task forces are also playing key roles [ 8 , 16 ]. Yet no reductions in the number of RTCR chest injury deaths have been observed throughout the study period, which underlines the importance of keep strengthening strategies to mitigate key risk factors and to improve road safety [ 17 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Blunt abdominal trauma is the leading cause of intra-abdominal injury with motor vehicle accidents being the leading cause of blunt abdominal trauma. Sports injuries and falls are some of the other causes (1) . Abdominal trauma is generally divided into blunt and penetrating trauma.…”
Section: Introductionmentioning
confidence: 99%